2022
DOI: 10.1186/s40659-022-00374-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal GRK2 regulates microglial activation and contributes to electroacupuncture analgesia on inflammatory pain in mice

Abstract: Background G protein coupled receptor kinase 2 (GRK2) has been demonstrated to play a crucial role in the development of chronic pain. Acupuncture is an alternative therapy widely used for pain management. In this study, we investigated the role of spinal neuronal GRK2 in electroacupuncture (EA) analgesia. Methods The mice model of inflammatory pain was built by subcutaneous injection of Complete Freund’s Adjuvant (CFA) into the plantar surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Studies have demonstrated that EA has an analgesic effect on chronic pain and can modulate mood changes and cognitive dysfunction through central and peripheral mechanisms ( Han, 2011 ; Chen et al, 2022 ; Zhou et al, 2022 ). In this study, EA had immediate alleviating effects on mechanical allodynia on postoperative day 7, and repeated EA alleviated the pT-ION-induced allodynia and anxiety-like behaviors on day 21 after nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that EA has an analgesic effect on chronic pain and can modulate mood changes and cognitive dysfunction through central and peripheral mechanisms ( Han, 2011 ; Chen et al, 2022 ; Zhou et al, 2022 ). In this study, EA had immediate alleviating effects on mechanical allodynia on postoperative day 7, and repeated EA alleviated the pT-ION-induced allodynia and anxiety-like behaviors on day 21 after nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that the mechanisms underlying the analgesic effect of EA are via the regulation of opioids, norepinephrine, or cholinergic activity in subcortical structures such as the spinal cord, periaqueductal gray matter, and hypothalamus pre-optic area [ 16 , 40 42 ]. However, whether the cerebral cortex is involved in the antihyperalgesic effects of EA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Recent research found that neuron GRK2 can specifically mediate the inhibitory effect of acupuncture on microglia activation and contribute to the analgesia of neuropathic pain 75 and inflammatory pain. 76 …”
Section: Discussionmentioning
confidence: 99%